Do Indian Firms Engage in Greenwashing? Evidence from Indian Firms - Sushobhan Sensharma; Manish Sinha; Dipasha Sharma (Australasian Accounting, Business and Finance Journal, 2022)
This study aims to look at ESG reporting in India through the lens of greenwashing, with a focus on the companies listed in the National Stock Exchange under the NIFTY 50 index using available ESG scores and assessments. Further, it aims to measure the indulgence of greenwashing by the companies. This study also analyses and attempts to highlight the factors that influence a company’s greenwashing behaviour, focusing specifically on the Indian context. Data for the empirical study and calculation of greenwashing score is collected from secondary data sources. We further use a regression method to study the nature of influence and significance of various factors on the calculated greenwashing score and assess the findings with our hypothesis. The study identifies 54% from the 48 companies, part of our sample size as green washers. Most of these companies belong to the manufacturing and energy sector of the Indian economy. The regression results suggest that a company’s cross listing status or its presence in any ESG focus fund has a significant and negative relationship with its observed greenwashing score. On firm level characteristics, the regression results indicate that a company’s board size and the presence of independent directors have a significant impact on the company’s observed greenwashing score.
Keywords: Sustainable Investing; ESG; Greenwashing; NIFTY 50; India